Analysis of Traders’ Satisfaction with the Quality of Beef Products at the Slaughterhouse of the Department of Food Security, Agriculture, and Fisheries (DKP3), Sragen Regency - Asykal Fira Yahya; Catur Suci Purwati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The quality of beef products plays an important role in determining trader satisfaction, especially in slaughterhouses that function as providers of safe, healthy, whole, and halal meat. However, several problems related to product quality, such as inconsistent color, fat content, and freshness, may lead to trader dissatisfaction. Therefore, it is necessary to analyze the level of product quality and its effect on trader satisfaction. The purpose of this study was to determine the level of beef product quality and trader satisfaction at the slaughterhouse managed by the Department of Food Security, Agriculture, and Fisheries of Sragen Regency. The research utilized a descriptive quantitative approach through a survey method. Information was gathered via a structured questionnaire featuring a Likert scale (1–5), which was given to 20 beef vendors. The analysis focused on variables such as product quality (including color, texture, marbling, smell, and freshness) as the independent variable and vendor satisfaction as the dependent variable. Data was examined using descriptive statistics along with simple linear regression. Findings indicated that vendors typically held a favorable view of the quality of beef products, as indicated by the prevalence of “agree” and “strongly agree” answers across all measured factors. The statistical analysis showed that product quality had a noteworthy positive effect on vendor satisfaction, indicated by a coefficient of determination (R²) of 0.915, suggesting that 91.5% of vendor satisfaction was affected by product quality. Furthermore, the regression analysis pointed to a significant connection (p < 0.05) between product quality and vendor satisfaction. In summary, the quality of beef products has a major impact on vendor satisfaction at the slaughterhouse. Thus, it is critical to uphold and enhance product quality to guarantee vendor satisfaction and maintain business viability.